Teachers' self-efficacy and the sources of efficacy: A cross-cultural investigation in Japan and Finland. (May 2019) - Yada, Akie; Tolvanen, Asko; Malinen, Olli-Pekka; Imai-Matsumura, Kyoko; Shimada, Hiroshi; Koike, Rihei; Savolainen, Hannu
Abstract: The study explores the extent and sources of Teachers' Self-Efficacy (TSE) for inclusive practices among 261 Japanese and 1123 Finnish teachers. Measurement invariance was tested to ensure the chosen scales' cross-cultural validity. In both countries, mastery experience was identified as the strongest of the four sources contributing uniquely to TSE. However, the two groups differed in how verbal persuasion predicted TSE. The findings indicate that the effects of the four sources on TSE depend strongly on sociocultural context, and that, in Japan, other sources may exert a powerful influence. Practical implications are discussed, with particular regard to teacher training programs. Highlights: Teachers' self-efficacy (TSE) and its sources were examined in Japan and Finland. Measurement invariance testing confirmed the scales' construct validity. Mastery experience made the strongest unique contribution to TSE in both countries. The influence of verbal persuasion on TSE differed between Japan and Finland. Sources other than those proposed byBandura (1977) may influence TSE in Japan.